Kemampuan pembiayaan perumahan untuk golongan bumiputera - Ismail, Azizah (2015)
Housing financing is one of the important mechanism that should be considered to meet housing needs. Housing financing problems do not only faced by the low income group, but also medium income. Various government initiatives are implemented to help the population, especially for the bumiputera to have their own houses. However, low purchasing power and difficulties in securing financing facilities caused bumiputera cannot afford to own a house at to their eligibility price. Thus, this study is conducted to identify the affordability level of housing financing in Iskandar Malaysia among the bumiputera buyers, determine the factors that influenced financing problems and determined the relationship between the purchase affordability with financing facilities. Data and information are collected through questionnaires and the data gathered then be analyzed by using descriptive analysis (frequency and Likert Scale), Cross Tabulation and Chi Square using SPSS software in order to get the final result. The findings show that bumiputera in the medium income group can only afford a house below RM250,000 with monthly installments below RM1,000. The main factors that influenced bumiputera housing financing problems are house prices too high, many restrictions imposed, the monthly installments and interest rates are too high, difficult to provide deposit, insufficient income, high expenditure patterns and housing policies constrain bumiputera to obtain financing. Factors that indicating a significant relationship is gender, marital status, age, employment sector, the number of households, availability of financing, the application process, types of employment, consumption patterns, income, government policy, home prices, monthly instalments, money deposit, loan term and financing costs. In addition, lack of communication channels is also a key factor of financing hard to come by. To overcome this problem, the government should set up a special facility to protect bumiputera rights, control house prices, establish central bank funding to assist bumiputera to own a house. In addition, new findings results of this study establish a framework for housing finance has helped bumiputera to afford a house according to their income.